HUBUNGAN FREKUENSI KONSUMSI MAYONES DENGAN KELUHAN DISPEPSIA FUNGSIONAL PADA PEGAWAI KANTOR - Ledo, Naldi; Setyawan, Yuswanto (Jurnal LENTERA, 2025)
Functional digestive disorders or dyspepsia are common complaints frequently experienced by office workers, mainly due to sedentary lifestyles and unhealthy eating patterns. One often overlooked trigger is the consumption of high-fat foods such as mayonnaise, which is commonly found in instant and fast foods. This community service activity was conducted in Pasuruan City with the aim of providing nutrition education and increasing awareness of the relationship between the frequency of mayonnaise consumption and symptoms of functional dyspepsia. The program included an initial questionnaire on mayonnaise consumption habits and digestive complaints, followed by interactive health education sessions, training on low-fat meal planning, simulations on how to read nutrition labels, and group discussions based on case studies. A total of 150 office employees actively participated in the two-day program. Data evaluation using Chi-square and Spearman correlation tests revealed a significant relationship between high-frequency mayonnaise consumption and the occurrence of dyspeptic symptoms such as nausea, epigastric pain, and bloating. Additionally, there was an observed increase in participants' nutritional understanding and their commitment to adopting healthier eating behaviors. These findings indicate that educational interventions in the workplace can be an effective strategy for preventing digestive disorders related to excessive fat intake.